2022
DOI: 10.3389/fpls.2022.930721
|View full text |Cite
|
Sign up to set email alerts
|

Gene network downstream plant stress response modulated by peroxisomal H2O2

Abstract: Reactive oxygen species (ROS) act as secondary messengers that can be sensed by specific redox-sensitive proteins responsible for the activation of signal transduction culminating in altered gene expression. The subcellular site, in which modifications in the ROS/oxidation state occur, can also act as a specific cellular redox network signal. The chemical identity of ROS and their subcellular origin is actually a specific imprint on the transcriptome response. In recent years, a number of transcriptomic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Glutathione S-transferases protect cells from oxidative damage by utilizing glutathione to scavenge reactive oxygen species (ROS) (S. Kumar & Trivedi, 2018). GSTU25 has been reported to be induced under oxidative, salt, and heat stresses (Sappl et al, 2009; Terrón-Camero et al, 2022). The convergent endodermal expression of GSTU25 in the two extremophytes might suggest a role of GSTU25 in ROS scavenging in endodermal cells, which may contribute to the salt tolerance in the two extremophytes.…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione S-transferases protect cells from oxidative damage by utilizing glutathione to scavenge reactive oxygen species (ROS) (S. Kumar & Trivedi, 2018). GSTU25 has been reported to be induced under oxidative, salt, and heat stresses (Sappl et al, 2009; Terrón-Camero et al, 2022). The convergent endodermal expression of GSTU25 in the two extremophytes might suggest a role of GSTU25 in ROS scavenging in endodermal cells, which may contribute to the salt tolerance in the two extremophytes.…”
Section: Resultsmentioning
confidence: 99%
“…Under abiotic stress conditions, the accumulation of unfolded or misfolded proteins in the ER can lead to ER stres 25 . Li et al also found that the upregulation of ER protein processing in maize was most significant after high-temperature stress, which was consistent with our research results 26 .…”
Section: Discussionmentioning
confidence: 99%
“…), primarily those represented in core DEGs of ROS Wheel Cluster III 15 . The ROS Cluster III genes are typical of a rapidresponse to high intensity light and are also represented in the rapid oxidative stress response of peroxisome-dependent genes 32 . The predominance of this category of ROS genes suggests that rapid changes in the gravity environment are perceived by plants as an acute stress requiring mitigation though the ROS signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%